"High fuel efficiency is good for the environment": Balancing gains in fuel efficiency against trends in absolute consumption in the passenger aviation sector. Issue 11 (3rd November 2021) - Dobruszkes, Frédéric; Ibrahim, Charbel
Abstract: Following mounting concerns about climate change induced by commercial flights, the aviation industry has reacted with narratives that emphasize the increase in fuel efficiency (fuel/passenger-km) of its operations. However, climate change is due to absolute fuel burnt. In this regard, this article compares trends in fuel efficiency with absolute fuel burnt considering passenger flights from nine European airports in 2018 versus 1996. Within this sample, this article found that fuel/seat-km over this period decreased by about 30%, while the absolute fuel burnt increased 2.5 times. An exploration of the drivers of this increase revealed that it occurred in the provision of air services on preexisting and new routes mostly longer than 1, 000 km. Low-cost carriers were a significant contributor to this growth if one considers relative terms and smaller airports, but not absolute terms. These results question the ability of high-speed rail to significantly offset the impacts of aviation on climate.